Nonlinear Inferences on European Banking Resilience in Operating Efficiency and Riskiness Around the Financial Crisis - Tripathi, M.; Tavana, M., Frost, T.; Cvetkoska, Violeta (EURO, 2024)
We examine European banks’ financial performance and risk management and their trends over the years and across banking characteristics around the financial crisis of 2007-2008. By testing for the linear and nonlinear variations using an exogenous quasi-experiment design, we demonstrate the usefulness of understanding the cause of variations in banks’ operating efficiency and riskiness. We adopt the positive theory of capital allocation decisions and risk-taking activities to assess the relationship between banks’ efficiency and risk with value creation from intermediation services. First, we peer-benchmark banks’ efficiency, using data envelopment analysis, and obtain Fitch risk ratings to test for their yearly and geographical resilience, including linear and nonlinear variations before and after the crisis. Second, we de termine bank-specific and industry-specific operational and financial factors, including longitudinal and cross-sectional heterogeneities, that affect European banks’ operating efficiency and riskiness. We find that banking efficiency can provide intuition on mitigating excessive investments and risk-taking around the financial crisis. Further, we capture the informational relevance of banking efficiency to third-party agencies in assessing financial strengths and credit risks. Our study provides a foundation to examine variations in European banks’ performance and risk realizations, including financial decisions and operating saliency.
https://euro2024cph.dk/programme/conference-program